Predictive value of C-reactive protein in patients with unstable angina pectoris undergoing coronary artery stent implantation - Karaca, I; Aydin, K; Yavuzkir, M; Ilkay, E; Akbulut, M; Isik, A; Arslan, N (Sage Publications Ltd, 2005)
In-stent restenosis is a major problem following coronary stent implantation, and inflammation plays an active role. We evaluated the effectiveness of the inflammatory marker C-reactive protein (CRP) as a predictor of in-stent restenosis after successful stent implantation, in 86 patients with unstable angina pectoris. Plasma CRP was measured in all patients before the procedure, and at 48 - 72 h and 1, 2 and 3 months post-procedure. An angiographic loss of 50% at follow-up was accepted as in-stent restenosis. We found negative and positive predictive values of the pre-procedural plasma CRP for determining 6-month in-stent restenosis of 34% and 61%, respectively. We also found a strong correlation between the 3-month post-procedural CRP value and 6-month in-stent restenosis; the negative and positive predictive values being 8% and 76%, respectively. In conclusion, we showed that a plasma CRP value > 3 mg/l in the third month after coronary stent implantation was a strong predictor of angiographic in-stent restenosis.
74th Congress of the European-Atherosclerosis-Society -- APR 17-24, 2004 -- Seville, SPAIN
Keywords: in-stent restenosis; inflammation; C-reactive protein (CRP)